Design study of auxiliary power supply system for a Malaysian 26M steel trawler - Nurulhuda Abd. Ghafar, 1984-; Nasrudin Ismail, supervisor; Fakulti Kejuruteraan Mekanikal (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2008